MCM5 Aggravates the HDAC1-Mediated Malignant Progression of Lung Cancer - Zhang, Lin-lin; Li, Qi; Zhong, Dian-sheng; Zhang, Wei-jian; Sun, Xiao-jie; Zhu, Yu (Frontiers in Cell and Developmental Biology, 2021)
Background Histone deacetylase 1 (HDAC1) is essential in the malignant progression of tumors. However, there is no obvious relationship between the expression of HDAC1 and the survival of lung cancer patients. Herein, we explored the involvement of minichromosome maintenance complex component 5 (MCM5) and HDAC1 interaction in the epithelial-to-mesenchymal transition (EMT)-dependent malignant progression of lung cancer. Methods We analyzed the expression of MCM5 and HDAC1 in The Cancer Genome Atlas database and clinical samples, as well as their impact on patient survival. Cell and animal experiments were performed to verify the promotion of EMT in lung cancer cells mediated by MCM5 and HDAC1. Results We found that lung adenocarcinoma patients with high expression of MCM5 and HDAC1 had poor survival time. Overexpression of MCM5 and HDAC1 in A549 and H1975 cells can promote proliferation and invasion in vitro and tumor growth and metastasis in vivo. Moreover, astragaloside IV can block the interaction between HDAC1 and MCM5, which can then inhibit the malignant progression of lung cancer in vivo and in vitro. Conclusion The interaction between MCM5 and HDAC1 aggravated the EMT-dependent malignant progression of lung cancer. Astragaloside IV can block the interaction between MCM5 and HDAC1 to inhibit the progression of lung cancer.